Randomized, Controlled Study of Adderall XR in ADHD - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2002)
The efficacy and safety of Adderall XR in the treatment of attention deficit/hyperactivity disorder and diurnal variation in responses were assessed by a multicenter, randomized, double-blind, parallel group, placebo-controlled trial at 47 sites, and reported from the Massachusetts General Hospital, Boston, MA.